Childhood abuse, neglect, household dysfunction, and juvenile recidivism: The mediating role of social bonds. (September 2022) - Craig, Jessica M.; Wolff, Kevin T.; Pierce, Kelly; Zettler, Haley; Baglivio, Michael T.
Abstract: Purpose: Though prior research has found a connection between Adverse Childhood Experiences (ACEs) and offending, only a few studies have investigated potential mediators that may help explain these effects. The current study builds upon childhood abuse research that has found social bonds to be a mediator between childhood maltreatment and offending and examines the extent to which social bonds represent an intervening variable between ACEs and recidivism. Methods: Using a sample of first-time adjudicated youth and an expanded measure of social bonds, a structural equation modeling (SEM) path analysis of the ACEs → social bonds → juvenile recidivism relationship was conducted. Results: The models revealed partial support for mediation- the indirect effect of ACEs on recidivism via social bonds was marginally significant. Further, it was found that 32% of the total effect of ACEs on recidivism operated through a youth's social bonds. Conclusions: These findings highlight one potential mechanism of the ACE-offending relationship and further implications of this indirect relationship are discussed. Highlights: This study examines if social bonds mediate the effect of trauma on recidivism. Structural equation models reveal partial support for mediation. Thirty-two percent of the ACEs effect on recidivism operated through social bonds.